Emulsion ionic liquid membranes (EILMs) for removal of Pb(II) from aqueous solutions - Lende, Avinash B.; Dinker, Manish K.; Bhosale, Vikas K.; Kamble, Sanjay P.; Meshram, Pawan D.; Kulkarni, Prashant S. (RSC Advances, 2014)
Ionic liquids (ILs) are playing increasingly important roles in the membrane separation processes. The present manuscript discusses the removal of Pb(II) ions from aqueous solution using an emulsion ionic liquid membrane (EILM) process. Initially, the emulsion liquid membrane (ELM) was prepared by stirring strip phase (sulphuric acid) and organic phase (surfactant: span 80, extractant: D2EHPA, diluent: hexane) together under high speed agitation. Note that, the parameters of the ELM process such as emulsification speed, pH of the feed phase, treat ratio, extractant and surfactant concentrations were studied for the maximum removal of Pb(II) ions. The role of IL was explored by adding hydrophobic IL, octylmethylimidazole hexafluorophosphine ([OMIM][PF6]), in the organic phase. The performance of ELM with and without IL was compared on the basis of stability, enrichment factor and the removal efficiency for Pb(II). The results showed that the percentage of Pb(II) extraction was complete by the emulsion membrane with IL (EILM) in comparison to the 97% achieved by neat ELM. Further, the stability and the enrichment factor of the EILM were found to be 2-3 times greater than that of the ELM. The FT-IR spectroscopic analysis revealed that bond interactions between IL and membrane phase components avoided the coalescence of internal phase droplets and enhanced the emulsion stability. The results obtained in this work support the use of the IL [OMIM][PF6] as both a stabilizer and carrier for the overall improvement of the ELM process.

Chitosan-based lead ion-imprinted interpenetrating polymer network by simultaneous polymerization for selective extraction of lead(ii) - Hande, Pankaj E.; Kamble, Sanjay; Samui, Asit B.; Kulkarni, Prashant S. (Industrial & Engineering Chemistry Research, 2016)
In this study, we report the synthesis of a Pb(II) ion-imprinted interpenetrating polymer network (II-IPN) by simultaneous polymerization for selective extraction of Pb(II) from printed-circuit-board (PCB) recycling unit wastewater. Initially, a polymer network was synthesized by polymerization of methacrylic acid (monomer) and ethylene glycol dimethacrylate (cross-linker) and a second polymer network by chitosan (complexing monomer) and tetraethyl orthosilicate (cross-linker). The chemical structure and morphology of the II-IPN were analyzed using Fourier transform infrared, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The interaction of the functionality in the II-IPN with Pb(II) through chelation was studied by X-ray photoelectron spectroscopy analysis. The maximum adsorption capacities for II-IPN and nonimprinted interpenetrating polymer network were 37.5 and 10.3 mg g(-1), respectively. The largest selectivity coefficient for Pb(II) in the presence of W(VI) was 161.58. The developed Pb(II) II-IPN was successfully employed for selective extraction of Pb(II) from PCB recycling unit wastewater.

Efficacy of zero-valent copper (Cu-0) nanoparticles and reducing agents for dechlorination of mono chloroaromatics - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2016)
The zero-valent copper (Cu-0) nanoparticles were prepared by chemical reduction method. The morphology of nanoparticles was investigated by using X ray diffraction, scanning electron microscopy-energy dispersive X ray, UV-visible spectrophotometer and Brunauer-Emmett-Teller surface area analyser. The Cu-0 nanoparticles along with reducing agents, NaBH4/5% acidified alcohol were used for the dechlorination of chloroaromatics at room temperature. Chlorobenzene (Cl-B), chlorotoluene (Cl-T), chloropyridine (Cl-Py) and chlorobiphenyl (Cl-BPh) were selected as the contaminants. The effect of various operating parameters such as pH, concentration of the catalyst and reducing agent (NaBH4), and recycling of the catalyst on dechlorination were studied. Nearly complete dechlorination of all the chloroaromatics were achieved in the presence of Cu-0 nanoparticles (2.5 g L-1) and NaBH4 (1.0 g L-1.) within 12 h. On the contrary, approximately 70% of dechlorination was observed in the presence of 5% acidified alcohol at similar experimental conditions. The dechlorination mechanism highlighted the importance of Cu-0 nanoparticles as a surface mediator. The kinetics of the dechlorination of chloroaromatics was investigated and compared with chloroaliphatics. The dechlorination rate differed from 0.23 h(-1) (Cl-B) to 0.15 h(-1) (Cl-BPh) in the presence of Cu-0 nanoparticles and NaBH4. The effectiveness of Cu nanoparticles with NaBH4 (1 g L-1) and 5% acidified alcohol as electron donors were studied by oxidation-reduction potential and observed to be -1016 mV and -670 mV, respectively. Final products of the dechlorination were benzene, toluene, pyridine and biphenyl, as identified by gas chromatograph mass spectrometer and nuclear magnetic resonance spectroscopy. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acidified alcohol; ChloroAromatics; Hydrodechlorination; NaBH4; Wastewater treatment; Zero-valent copper (Cu-0) nanoparticles

L-Proline functionalized dicationic framework of bifunctional mesoporous organosilica for the simultaneous removal of lead and nitrate ions - Dinker, Manish K.; Ajithkumar, Thalasseril G.; Kulkarni, Prashant S. (ACS Sustainable Chemistry & Engineering, 2017)
A novel bifunctional mesoporous organosilica, PEG-functionalized bis-prolinium chloride bridged mesoporous organosilica (BPBMO) was synthesized by reacting the precursor, PEG-functionalized bis-prolinium chloride bridged organosilane (BPRIL) with tetraethyl orthosilicate (TEOS) in the presence of surfactant. The chemical conformation of BPBMO was investigated by using Fourier transform infrared (FTIR), thermogravimentric analysis (TGA), C-13, and Si-29 cross-polarization/magic angle spinning (CP/MAS) NMR techniques. The characterization represents PEG-linked-prolinium (-N+Cl-) and carboxyl (-COOH) entities, constructing the dicationic framework through siloxane (Si-O-Si) linkages. The pore-wall distribution and the periodicity of BPBMO retained during the synthesis were examined by small-angle X-ray scattering (SAXS), Brunauer-Emmett-TellerBarrett-Joyner-Halenda (BET-BJH), and transmission electron microscopy (TEM) techniques. The results revealed BPBMO as a spherical shaped solid (50-100 nm) having mesopore channels hexagonally arranged with interparticle porosity (S-BET = 487 m(2)/g and D-BJH = 5.1 nm). The material has provided active binding sites for the simultaneous removal of NO3- and Pb2+ ions when introduced in the aqueous solutions of Pb(NO3)(2) (50 mg/L, pH 6). The removal of NO3- by ion-exchange with prolinium (-N+Cl-) entities and the electrostatic interaction of Pb2+ with carboxylate (-COO-) group were characterized by using Raman spectroscopy, ion chromatography, and X-ray photoelectron spectroscopy (XPS) technique. The maximum removal of NO3- and Pia' ions were achieved within 1 h of the adsorption reaction. The adsorption has followed the Langmuir isotherm model with the adsorption capacities (q(m)) of 23.04 and 21.92 mg/g for NO3- and Pb2+ ions, respectively. The efficiency of the adsorbent was also compared with other adsorbents. Further, the BPBMO material has depicted three consecutive adsorption/desorption cycles with negligible loss in the structural conformation.

Separation of nitroaromatics from wastewater by using supported ionic liquid membranes - Bhosale, Vikas K.; Chana, Harpreet K.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Journal of Water Process Engineering, 2019)
Nitroaromatics have been released into wastewater during its production and application, thus, contaminating the ecosystem. The stringent discharge limits of industrial effluents have led to the development of sustainable technologies for removal of nitroaromatics from wastewater. In the present investigation, separation of nitroaromatic compounds such as TNT, TNP and Tetryl from model wastewater was investigated by using supported ionic liquid membrane (SILM) process. Various aliquat 336 based ionic liquids (ILs) were synthesised and characterized, and immobilized in PTFE and PVDF supports for the preparation of SILMs. The key parameters such as type of IL and striping phase, feed phase pH, selectivity for SILM, extraction kinetics and reuse of SILM were studied, in detail. The size of IL-anion plays an important role in removal process. The SILM was found to be selective for TNP over other nitroaromatics. Maximum separation of TNP (< 95%) was achieved with IL, [A336][SCN] within 12 h. Selectivity and reuse of the membrane indicate the potential of SILM technology as a sustainable chemical process for the treatment of nitroaromatics contaminated wastewater.
Keywords: Ionic liquid; Membrane; Nitroaromatics; Separation; wastewater

Screening of zero valent mono/bimetallic catalysts and recommendation of Raney Ni (without reducing agent) for dechlorination of 4-chlorophenol - Raut, Sandesh S.; Shetty, Rohit; Raju, Nikhi Maria; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2020)
Chlorophenol (CP) is considered as environmentally hazardous material due to its acute toxicity, persistent nature and strong bioaccumulation. The dechlorination of 4-CP was investigated by using various catalysts such as bimetallic (Fe-0/Cu-0, Al-0/Fe-0), Pd/C, Raney Ni and Fe-0 at room temperature. Among the catalysts studied, Raney Ni proved to be very economical and efficient catalyst that worked without the use of an external reducing agent. The dechlorination of 4-CP by Raney Ni was therefore further explored. Complete dechlorination of 4-CP (30 mg L-1) was achieved in 6 hat an optimum Raney Ni catalyst loading of 3 g L-1. The effect of triethylamine (TEA) and tripropylamine (TPA) was also investigated and it was observed that 100% dechlorination is possible in presence of 45 mg L-1 of TEA. The kinetics of dechlorination of 4-CP was investigated and found to be first order with a rate constant of 0.017 min(-1) at 50 degrees C, and it enhances to 0.109 min(-1) with addition of TEA. In the absence of a reducing agent, acidic to neutral pH favors dechlorination of 4-CP. The final product of dechlorination was estimated to be phenol by performing HPLC, LCMS and NMR analysis. Based on the results, a probable dechlorination mechanism of 4-CP is also proposed. It can be concluded that the catalytic hydrodechlorination is an effective and economical technique for dechlorination of 4-CP and it has a potential for the dechlorination of other toxic derivatives of chlorinated aromatics. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 4-Chlorophenol; Cl- scavenger; Hydrodechlorination; Raney Ni; Recycling of catalyst; Without reducing agent

Improved photocatalytic efficiency of TiO2 by doping with tungsten and synthesizing in ionic liquid: precise kinetics-mechanism and effect of oxidizing agents - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Environmental Science and Pollution Research, 2021)
The degradation of nitroaromatics/toxic energetic compounds contaminated water is a major cause of concern. W-doped TiO2 nanoparticles (NPs) were synthesized in ionic liquid, ethyl methyl imidazolium dicyanamide (EMIM-DCA) by a solvothermal method. The developed NPs were sintered at 500 degrees C and characterized by UV-Vis-DRS, FT-IR, FE-SEM, XRD, XPS, and BET techniques. The 30-40-nm-sized NPs were subjected to photocatalytic degradation of the toxic energetic compound, tetryl (2,4,6-trinitrophenylmethylnitramine) under UV-Vis light. Various operating parameters such as the effect of concentration of catalyst, pH of feed phase, oxidizing agents, and recycling of catalyst were studied in detail. For the first time, the degradation-mechanism pathway and kinetics of tetryl were evaluated. The degradation products were precisely analyzed by using HPLC, GC-MS, and TOC techniques. The USEPA has prescribed a drinking water limit of 0.02 mg L-1, and it was found that 0.5 g of 4% W-TiO2 could totally degrade tetryl (50 mg L-1) within 8 h. The kinetic rate constant of 4% W-TiO2 was 0.356 h(-1), whereas pure TiO2 showed 0.207 h(-1).
Keywords: Ionic liquid; Nitroaromatics; Photocatalysis; Recycling of catalyst; W-doped TiO2; wastewater

Hydrodechlorination of 4-chloro-2-aminophenol into a recyclable product using Ni- and Cu-based catalysts - Shetty, Rohit R.; Raut, Sandesh S.; Kulkarni, Prashant S.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2022)
The 4-chloro-2-amino phenol (4C2AP) bearing wastewater is produced while manufacturing dyes and pharma-ceutical ingredients. Ni-and Cu-based cost-effective catalysts were developed, typically characterized, and subjected to hydrodechlori-nation (HDC) of 4C2AP. The role of reducing agents, concentration, pH of wastewater, presence of salt, reaction temperature, catalyst reuse, and the kinetics was investigated. A selective makeover of 2-amino phenol (2AP) was analyzed by HPLC, LCMS, and NMR. A complete HDC of 4C2AP with remarkable selectivity (98%) toward 2AP was achieved using a Ni0 catalyst and NaBH4 at room temperature. It is observed that the alkaline condition, the presence of salt, and a high reaction temperature favor the HDC process. A maximum of 1 g L-1 of the Ni0 loading is found to be sufficient to dechlorinate the pollutant. It can be concluded that the catalytic HDC is a technically viable and inexpensive process for the conversion of 4C2AP into a valuable product, 2AP.

Tetraalkylammonium-based dicationic ionic liquids (ILs) for CO2 capture - Kulkarni, Prashant S.; Ranjane, Prathamesh; Mishra, Karun; Sundararajan, Swati; Kamble, Sanjay (New Journal of Chemistry, 2023)
This investigation includes the synthesis and characterization of a new series of ionic liquids (ILs) based on the tetraalkylammonium dication for the absorption of CO2, a step towards the development of more efficient and sustainable technologies. It was possible to synthesize amine-substituted PEG diacrylate by modifying poly(ethylene glycol) (PEG), which was then quaternized with 1-bromopentane to produce the IL PDBr. The other IL products, PDNTf2, PDBF4 and PDPF6, were synthesized via the metathesis of PDBr with the appropriate salt. The synthesized products were characterized using various techniques, such as FTIR, H-1 and C-13 NMR, elemental analysis, and density and viscosity meters, and evaluated as potential sorbents for CO2 capture. DSC and TGA were used to examine the thermal properties of the ILs. As observed from their thermal degradation behavior, the ILs exhibited two-stage disintegration with thermal stability up to 150 & DEG;C. The pressure drop method was used to study the sorption capacity of the ILs towards CO2. The sorption investigation showed that when the pressure is increased, the CO2 absorption increases. Equilibrium is reached in 40 minutes, demonstrating a rapid absorption rate. The IL with the [BF4](-) anion (PDBF4) demonstrated a maximum sorption capacity of 0.577 mole fraction of CO2, and can be regenerated and reused efficiently with less than 0.5% variation from its original absorption capacity. The CO2 absorption capacity for the ILs with other anions follows the trend: Br & AP; NTf2 < PF6 < BF4. This work shows that tetraalkylammonium-based dicationic ILs are adaptable, making them a suitable material for many applications, including sustainable CO2 capture technology.